Analisis Faktor-Faktor Yang Mempengaruhi Return On Assets Perusahaan - Dede Hertina; Sakina Ichsani; Gita Genia Fatihat; Yana Hendayana; John Henry Wijaya; R Susanto Hendianto (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The purpose of this study was to analyze the factors that affect ROA and to find out how much influence the independent variables: quick ratio, total assets turnover, fixed assets turnover, accounts receivable turnover, and debt ratio; had on return on assets. To achieve the research objectives, a sample of companies listed in the building construction sub-sector on the Indonesia Stock Exchange for the 2019-2021 period was used, with a total sample of 10 companies selected using a purposive sampling technique. This study uses panel data regression analysis to determine the effect of each independent variable on ROA. The results showed that the quick ratio, fixed assets turnover, accounts receivable turnover, and debt ratio did not have a positive effect on ROA. Meanwhile, total assets turnover has a positive effect on return on assets. The results of this study are expected to be information in determining the company's return on assets and it is expected that the company can consider the factors that affect the ROA, especially the total assets turnover factor.